Twenty‐First Century Drought Projections in the CMIP6 Forcing Scenarios. Issue 6 (1st June 2020) - Cook, B. I.; Mankin, J. S.; Marvel, K.; Williams, A. P.; Smerdon, J. E.; Anchukaitis, K. J.
Abstract: There is strong evidence that climate change will increase drought risk and severity, but these conclusions depend on the regions, seasons, and drought metrics being considered. We analyze changes in drought across the hydrologic cycle (precipitation, soil moisture, and runoff) in projections from Phase Six of the Coupled Model Intercomparison Project (CMIP6). The multimodel ensemble shows robust drying in the mean state across many regions and metrics by the end of the 21st century, even following the more aggressive mitigation pathways (SSP1‐2.6 and SSP2‐4.5). Regional hotspots with strong drying include western North America, Central America, Europe and the Mediterranean, the Amazon, southern Africa, China, Southeast Asia, and Australia. Compared to SSP3‐7.0 and SSP5‐8.5, however, the severity of drying in the lower warming scenarios is substantially reduced and further precipitation declines in many regions are avoided. Along with drying in the mean state, the risk of the historically most extreme drought events also increases with warming, by 200–300% in some regions. Soil moisture and runoff drying in CMIP6 is more robust, spatially extensive, and severe than precipitation, indicating an important role for other temperature‐sensitive drought processes, including evapotranspiration and snow. Given the similarity in drought responses between CMIP5 and CMIP6, we speculate that both generations of models are subject to similar uncertainties, including vegetation processes, model representations of precipitation, and the degree to which model responses to warming are consistent with observations. These topics should be further explored to evaluate whether CMIP6 models offer reasons to have increased confidence in drought projections. Plain Language Summary: Drought is an important natural hazard in many regions around the world, and there are significant concerns that climate change will increase the frequency or severity of drought events in the future. Compared to a world before anthropogenic climate change, the latest state‐of‐the‐art climate model projections from CMIP6 show robust drying and increases in extreme drought occurrence across many regions by the end of the 21st century, including western North America, Central America, Europe and the Mediterranean, the Amazon, southern Africa, China, Southeast Asia, and Australia. While these changes occur even under the most aggressive climate mitigation pathways, the models show substantial increases in the extent and severity of this drying under higher warming levels, highlighting the value of mitigation for reducing drought‐based climate change impacts. Given the significant response to even modest warming, however, and evidence that climate change has already increased drought risk and severity in some regions, adaptation to a new, drier baseline will likely be required even under the most optimistic scenarios. Key Points: The sign and magnitude of drought responses in the CMIP6 projections depend on the region, season, and drought metric being analyzed Soil moisture and runoff drying is more widespread and robust than precipitation, with the severity increasing strongly with warming The sign of CMIP6 responses aligns with previous results from CMIP5, suggesting similar physical processes and underlying uncertainties